High-Throughput Analysis of Water-Soluble Forms of Choline and Related Metabolites in Human Milk by UPLC-MS/MS and Its Application - Hampel, Daniela; Shahab-Ferdows, Setareh; Nguyen, Ngoc; Kac, Gilberto; Allen, Lindsay H. (Frontiers in Nutrition, 2021)
Choline and related metabolites are key factors in many metabolic processes and insufficient supply can adversely affect reproduction and fetal development. Choline status is mainly regulated by intake, and human milk is the only choline source for exclusively-breastfed infants. Further, maternal status, geno- and phenotype, as well as infant outcomes have been related to milk choline concentrations. In order to enable the rapid assessment of choline intake for the exclusively breastfeeding infant, and the further investigation of associations between milk choline and maternal and infant status and other outcomes, we have developed a simplified method for the simultaneous analysis of human milk choline, glycerophospho-choline, phospho-choline, and the less abundant related metabolites betaine, carnitine, creatinine, dimethylglycine (DMG), methionine, and trimethylamine N-oxide (TMAO) using ultra-performance liquid-chromatography-tandem mass-spectrometry (UPLC-MS/MS). These analytes have milk concentrations ranging over 3 orders of magnitude. Unlike other recently described LC-based methods, our approach does not require an ion-pairing reagent or high concentrations of solvent modifiers for successful analyte separation, and thus avoid signal loss and potential permanent contamination. Milk samples (10µL) were diluted (1:80, v:v) in water:methanol and filtered prior to analysis with an optimized gradient of 0.1% propionic acidaq and acetonitrile allowing efficient separation and removal of contaminants. Recovery rates ranged from 108.0-130.9% (inter-day variation: 3.3-9.6%), and matrix effects (ME) from 54.1-114.3%. MEs were greater for carnitine, creatinine and TMAO at lower dilution (1:40, p<0.035 for all), indicating concentration-dependent ion suppression. Milk from Brazilian women (2-8d, 28-50d, 88-119d postpartum, ntotal=53) revealed increasing concentration throughout lactation for glycerophospho-choline, DMG, and methionine, while carnitine decreased. Choline and phospho-choline were negatively correlated consistently at all 3 collection time intervals. The method is suitable for rapid analysis of human milk water-soluble forms of choline as well as previously not captured related metabolites with minimal sample volumes and preparation.